Peculiarities of aqua fitness exercises influence on the physical preparedness of women 30-49 years old using endogenous-hypoxic breathing method - S.V. Salnykova; Yu.M. Furman; A.S. Sulyma; I.V. Hruzevych; N.V. Gavrylova; V.Ye. Onyschuk; O.Yu. Brezdeniuk (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Aim: To establish the complex influence of aqua fitness exercises and endogenous-hypoxic breathing techniques on the physical preparedness of women 30-49 years old. Material: The study involved 41 women who had no previous experience of systematic physical education. 2 groups were formed: MG1 (n = 20, age 30-36 years old); MG2 (n = 210, age 37-49 years old). The experiment lasted for 24 weeks. At classes, aqua fitness was applied to the method of endogenous-hypoxic respiration. At the various stages of the study (8, 16 and 24 weeks) it was examined physical preparedness of women. Frequency of classes was 3 times a week. Results: Indicated in the need for dosage loading, taking into account the age factor and the level of physical and functional preparedness of women. It was established that classes contribute to improvement: explosive force; active flexibility of the spine; force dynamic endurance of the muscles of the lower extremities; speed-strength endurance of muscles of the abdominal press; power static endurance of muscles of the back, neck and buttock muscles; overall endurance. Conclusions: aqua fitness exercises together with the endogenous-hypoxic respiration method contribute to the improvement of the physical fitness of mature women. For women of 30-36 years old, improvements in physical fitness were reported earlier compared with older women.